Profil Pelajar Pancasila dan Implikasinya terhadap Peningkatan Motivasi Belajar Siswa - Mardiana, Dina; Amalia, Sofa (JOM, 2024)
The Pancasila Student Profile Strengthening Project (P5) is a project-based co-curricular activity designed to build student character based on Pancasila values. The exciting issue of implementing the independent curriculum lies in students' character and soft skills development dimensions, framed in a competency and character-strengthening project following the Pancasila student profile. In the context of implementation in driving schools, P5 is the spirit for the real implementation of the independent curriculum. This article empirically examines the implementation of P5 and its implications for increasing students' learning motivation at SMKN 4 Malang to obtain a critical analysis that can analyze the implementation process within the framework of implementing a quality independent curriculum. Based on a qualitative approach with a case study type, this research found that students at SMKN 4 Malang who internalized and applied Pancasila values ​​had higher learning motivation. The research conclusion is that through P5 habituation, the dimensions of independence and cooperation are proven to be key factors that increase students' enthusiasm and initiative in the learning process. This is proven by the successful achievement of work projects through the regular "Vocational School 4 Malang Learning Work Exhibition" with several indicators: 1). Student collaboration between departments in creating interactive reading book projects; 2). Cohesiveness and independence in working on project outputs according to each assignment through class collaboration between departments. Thus, developing the Pancasila student profile is important for forming student character and increasing learning motivation and the overall quality of education.